Fast and high-resolution mapping of elastic properties of biomolecules and polymers with bimodal AFM. Issue 12 (December 2018) - Benaglia, Simone; Gisbert, Victor; Perrino, Alma; Amo, Carlos; Garcia, Ricardo
Abstract Fast, high-resolution mapping of heterogeneous interfaces with a wide elastic modulus range is a major goal of atomic force microscopy (AFM). This goal becomes more challenging when the nanomechanical mapping involves biomolecules in their native environment. Over the years, several AFM-based methods have been developed to address this goal. However, none of these methods combine sub-nanometer spatial resolution, quantitative accuracy, fast data acquisition speed, wide elastic modulus range and operation in physiological solutions. Here, we present detailed procedures for generating high-resolution maps of the elastic properties of biomolecules and polymers using bimodal AFM. This requires the simultaneous excitation of the first two eigenmodes of the cantilever. An amplitude modulation (AM) feedback acting on the first mode controls the tip–sample distance, and a frequency modulation (FM) feedback acts on the second mode. The method is fast because the elastic modulus, deformation and topography images are obtained simultaneously. The method is efficient because only a single data point per pixel is needed to generate the aforementioned images. The main stages of the bimodal imaging are sample preparation, calibration of the instrument, tuning of the microscope and generation of the nanomechanical maps. In addition, with knowledge of the deformation, bimodal AFM enables reconstruction of the true topography of the surface. It takes 9 h to complete the whole procedure. This protocol describes how to generate high-resolution maps of the elastic properties of biomolecules and polymers using bimodal AFM. The procedure covers sample preparation, bimodal AFM setup and calibration, and data acquisition and processing.